ANALISIS PENGEMBANGAN USAHA BENIH IKAN AIR TAWAR DALAM MENINGKATKAN PENDAPATAN - Makmur Kambolong; Sahrun; Candra Puspita Ningtyas; Munawir Makmur; Nursia Darwis (Halu Oleo University, 2023)
This paper aims to determine the Analysis of Freshwater Fish Seed Business Development in Increasing Income (Study at UPTD Fish Seed Center in Rahandouna Village, Poasia District, Kendari City). The research method uses a qualitative descriptive approach and collects data through interviews, observation and document studies. Sources of data from research informants and secondary data that are relevant to research studies. Using interactive data analysis model data analysis techniques from Miles, Huberman & Saldaña (2014)The results of the study show that business development in freshwater fish hatcheries in Rahandouna Village, Poasia District, Kendari City can be said to experience development and increase in income where the business location has experienced additions from initially there were only 1-20 ponds to 30 ponds, and a workforce that was initially only 3 employees to 5 employees. In this case, business capital has increased from Rp. 35,000,000 to Rp. 50,000,000 initially